Detection of HPV by polymerase chain reaction (PCR) in paraffin embedded cervical cancer tissue - Olszak, Agnieszka; Kulig, Andrzej; Smolarz, Beata; Kozłowska, Elżbieta (Menopause Review/Przegląd Menopauzalny, 2003)
Purpose. Epidemiological studies showed that infections with several types of Human Papillomavirus (HPV) are the main risk factor for the development of cervical carcinoma. Materials and methods. In the present work the infection of high risk as well as low risk HPV in subjects with cervical cancer were investigated. Paraffin embedded tumour tissues were obtained from 22 women with cervical carcinoma. The HPV appearance was determined by PCR amplification using the appropriate primers. Results. The high risk HPV was detected in 82% (18/22) of cervical cancer patients and low risk HPV in 18% of cervical cancer patients (4/22). The number of samples with high risk HPV was significantly higher than low risk samples (P <0.05). Conclusion. The PCR is a rapid and sensitive method for the detection of HPV in paraffin embedded cervical cancer samples.